The performance of the computer software and services sector in Argentina: Microeconometric evidence on public-sector support programmes - Mariano Pereira; María Florencia Barletta; Gabriel Yoguel (CEPAL Review, 2016)
This article analyses the impact of public-sector support programmes on the recent performance of the computer software and services sector in Argentina. First, the effect of these programmes on firms’ innovation performance is studied, with a propensity score matching technique used to calculate the average treatment effect on treated firms. The results confirm that receiving public funds had a positive impact on the ratio between research and development (R&D) spending and sales, employment in R&D and the propensity to introduce new products or processes. The effect of policy intervention on firms’ economic performance is then analysed, with an instrumental variables design being used in this case. The results show a positive impact on the propensity to export, export intensity and employment growth.